Stromatolite research in the Shark Bay World Heritage Area - Collins, Lindsay; Jahnert, Ricardo (Royal Society of Western Australia, 2014)
Three decades after declaration of World Heritage status for Shark Bay new research findings are being reported on the specialised microbial habitats that characterise its hypersaline settings, the composition of microbial communities, tidal flat evolution, stromatolite geochronology and subtidal microbial systems. In the stable, semiarid and evaporative setting within the intertidal–subtidal environment the microbial ecosystem is trapping, binding and biologically inducing carbonate precipitation within laminated stromatolites, non-laminated thrombolitic forms and cryptomicrobial non-laminated forms. Filamentous microbes constitute the dominant group in the blister, tufted and smooth mat types, and coccoid microbes dominate the pustular, colloform and microbial pavement deposit types. Detailed georeferenced substrate mapping has revealed extensive subtidal microbial deposits occupying ~300 km2 of the total Holocene 1400 km2 area of Hamelin Pool. The microbial pavement covers 227 km2 of the subtidal substrate, which together with columnar structures reveals a subtidal microbial habitat that occupies an area several times larger than the area of the intertidal deposits.Oldest dated stromatolite heads are 1915 14C years BP, and the overall system was deposited in two stages: the first between 2000 and 1200 and the last from 900 years BP to the present. Slow accretion rates vary from less than 0.1 to 0.5 mm/year. Different internal fabrics were constructed according to their position in relation to the littoral zone by distinct microbial communities, and lateral fabric relations have been established. Evidence of shallowing-upward fabric sequences of microbial origin reflects relative falling sea levels during the late Holocene and is likely useful in ancient environmental interpretation. A new substrate map and depositional history for this distinctive microbial habitat has established the significance of subtidal structures and emphasises the geoscientific importance of Hamelin Pool, especially with respect to early life studies and ancient analogues for understanding microbial activity, deposit characteristics, fenestral fabrics and distribution.